THE EFFECTIVENESS OF WORDFAST TRANSLATION MEMORY TO IMPROVE THE STUDENTS' TRANSLATION QUALITY IN TRANSLATING REPETITIVE TEXTS : A Pre-experimental study of the 7th Semester students of The English Language and Literature Program in UPI Bandung - Fitra Lugina, - (2005)
The research is designed to prove the hypothesis that there is a significant contribution given by Wordfast Translation Memory (TM) software to the improvement of the student translation quality. The method used is the pre-experimental design. The research compares the mean from the pre-test (translation test without Wordfast) and the post-test (translation test with Wordfast) result. 30 students of the 7th semester students of English Language and Literature Program are involved in this research. They are divided into two groups; the tryout group (10 students) and the experimental group (20 students). The subjects of the research are the experimental group only, where the tryout group is intended to find the validity and the reliability of the instruments. The instruments used are tests; pre-test and post-test which is exactly the same. The pre-test and post-test were given to the experimental group and the significance result appears after the comparison of the pre-test and the post-test mean. The duration of the training of the wordfast usage in the experimental group was three days. The mean comparison shows that there is an improvement in the students translation quality score, from 128,85 in pre-test to 144,35 in post-test. The translation quality indicators average score comparison shows that there are significant improvement in Accuracy, Clarity and Naturalness score. The dependent t-test calculation shows that the derived t value is -6,911 which is exceed the tcnt value of ± 2,091 at a = 0,05 with df=19. By this reason, the H0 is rejected and the Ha is retained. Furthermore the effect determination calculation shows that the rvalue is 0,85. It means that the Wordfast TM usage has large effect in increasing the students' translation quality. Based on the research calculations, it can be concluded that the Wordfast usage in translation process is significant in increasing the students' translation quality.